Future global distribution and climatic suitability of Anopheles stephensi - Andre Luis Acosta; Marcia C. Castro; Gabriel Z. Laporta; Jan E. Conn; Maria Anice M. Sallum (Scientific Reports)
Abstract Anopheles stephensi, an urban malaria vector, is expanding into new regions and poses a growing global health threat. Using a robust multi-model framework with eight algorithms and high-resolution climate data, this study assessed and mapped current and future global climate suitability for the species, incorporating demographic data to estimate populations at risk in different scenarios. Currently, An. stephensi can thrive in 13% of the Earth’s surface, affecting nearly 40% of the global population. Projections indicate that suitable areas could exceed 30% by 2100, exposing up to 56% of the world’s population, including in previously malaria-free regions such as North America, Europe, and Oceania. Spread may occur via maritime traffic, wind dispersal, and natural range expansion. These findings highlight the urgent need for global monitoring and control strategies, emphasizing the importance of integrating climate change projections into urban malaria prevention efforts to protect vulnerable populations and support global malaria elimination goals.